For the Liberation of the Indians (International review of mission, 1971)
From January 25th to 30th 1971, a group of anthropologists and sociologists participated in a Symposium on Inter-Ethnic Conflict in South America held in Barbados, West Indies. This meeting was sponsored by the Programme to Combat Racism and the Commission of the Churches on International Affairs of the World Council of Churches, and also by the Institute of Ethnology of the University of Bern, Switzerland. The group analysed several prepared reports on the situation of indigenous populations in many Latin American countries. A report of the Symposium is being prepared for publication, probably in July 1971. It is hoped to review this report in the IRM and to publish comments and reactions from those involved in mission among Latin American Indians. In the first instance, however, the participants decided to prepare and publish a statement in order to define and clarify the issues involved as a contribution to the struggle of the Indians for liberation. The following statement, therefore, represents the considered views of the members of the Symposium and not of the World Council of Churches. As such it is offered for discussion and comment. Editor